Refleksi Budaya Muslim Pada Adat Perkawinan Budaya Banjar Di Kota Samarinda - Noorthaibah, Noorthaibah (FENOMENA, 2012)
Process of Islamization in Indonesia that has characteristic, namely; runs in peace, follows customary, soaks into clefts of facets of Indonesian nation life in each facet of life through the planting path of religion values on the customary local culture. The process of Islamization in Indonesia was lasting in such a long periods to hundreds of years. According to the history, East Kalimantan was being Islam firstly by Datuk Ri Bandang and Tunggang Parangan. Process of Islamization in Kutai and the surrounding area was predicted to happen about 1575. The Islamization process of Banjarnesesociety spreads peacefully, seeps into the clefts of life in every aspect, adapts itself in the local culture. It unites and integrates the Islamic values into the culture system. Thus the local culture that used to be animism primitive is changed to be a new culture, which is Islamic culture. Islamic culture in Banjarnese customary reflected as the marriage ceremony in the form of symbol, the society behavior and also the tool used, although the Islamic reflection is rudimentary but as other cultures that characterized selective dynamic then in fact, the customary of Banjarnese culture is growing into a form of value improvement that is more Islamic.